A Comparative Analysis of the Risk Profiles of Australian Young Offenders From Rural and Urban Communities. (October 2019) - Butcher, Luke; Day, Andrew; Miles, Debra; Kidd, Garry
Australian young people from rural areas, particularly Aboriginal young people, are overrepresented in the juvenile justice system. Apart from broad evidence regarding the entrenched social disadvantages experienced by young people in rural communities, the literature is limited in describing why this might be case. Due to these social disadvantages, it is hypothesised that young offenders from rural communities will have higher levels of offending risk factors, as measured by the Youth Level of Service/Case Management Inventory—Australian Adaption (YLS/CMI-AA). A total of 6, 750 archival records were analysed, showing that significantly more Aboriginal young offenders live in rural areas. Contrary to the hypothesis, urban young offenders had significantly higher risk scores than rural young offenders. These findings suggest that there may be particular ecological factors that are not assessed in the current risk assessment instrument or that rural young people have a range of protective factors that may insulate against the broader context of social disadvantage.